2017
DOI: 10.1186/s12864-016-3428-1
|View full text |Cite
|
Sign up to set email alerts
|

Integrated RNA-seq and DNase-seq analyses identify phenotype-specific BMP4 signaling in breast cancer

Abstract: BackgroundBone morphogenetic protein 4 (BMP4) plays an important role in cancer pathogenesis. In breast cancer, it reduces proliferation and increases migration in a cell line-dependent manner. To characterize the transcriptional mediators of these phenotypes, we performed RNA-seq and DNase-seq analyses after BMP4 treatment in MDA-MB-231 and T-47D breast cancer cells that respond to BMP4 with enhanced migration and decreased cell growth, respectively.ResultsThe RNA-seq data revealed gene expression changes tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 69 publications
4
16
0
Order By: Relevance
“…While associations between different molecular levels (e.g., RNA on protein expression, chromatin accessibility on RNA expression) were generally strongest at the same time point, we identified long-lasting effects across and within regulatory layers, which seem to prepare the cell for differentiation processes already at the exit from pluripotency. It further revealed that chromatin accessibility at gene promoters is necessary but not sufficient for productive gene expression, which has been reported in other systems such as response to BMP4 signaling in cancer (Ampuja et al, 2017). This could indicate that developmental gene promoters are already primed by pluripotency factors before developmental TFs bind them.…”
Section: Discussionmentioning
confidence: 57%
“…While associations between different molecular levels (e.g., RNA on protein expression, chromatin accessibility on RNA expression) were generally strongest at the same time point, we identified long-lasting effects across and within regulatory layers, which seem to prepare the cell for differentiation processes already at the exit from pluripotency. It further revealed that chromatin accessibility at gene promoters is necessary but not sufficient for productive gene expression, which has been reported in other systems such as response to BMP4 signaling in cancer (Ampuja et al, 2017). This could indicate that developmental gene promoters are already primed by pluripotency factors before developmental TFs bind them.…”
Section: Discussionmentioning
confidence: 57%
“…They are significantly upregulated in late stage of HCC. One of the studies reveals the role of RP3-375P9.2 in breast cancer [63].…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…A number of studies have examined TFs in the context of BMP signaling but lack direct evidence of interaction with SMAD proteins. [41][42][43][44] For example, HOX, SOX, FOX, bHLH, POU, and NR3C1 TFs were implicated as master regulators of the specificity of the BMP signaling response at different stages of hair follicle development. 44 In breast cancer cells, MDB2…”
Section: Smad-interacting Tfs Of the Bmp Pathwaymentioning
confidence: 99%
“…was implicated as a common transcriptional activator of BMP4 specific target genes. 42 Interestingly, CBFB functioned as a transcriptional activator in breast cancer cells where BMP4 treatment induces proliferation whereas HIF1A was a transcriptional repressor in cells with induced migration phenotype. 42 Here we focus on those TFs that have been experimentally validated to interact with SMADs upon stimulation of the BMP pathway.…”
Section: Smad-interacting Tfs Of the Bmp Pathwaymentioning
confidence: 99%
See 1 more Smart Citation